Makna Kepuasan Kerja bagi Pegawai Kampus OTC: Studi Kualitatif tentang Lingkungan Kerja, Kompensasi, Kepemimpinan, dan Pengembangan Karier - Ngakan Putu Purwita (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the factors influencing job satisfaction among employees at OTC Campus, with a focus on the meanings perceived by employees regarding the work environment, compensation, leadership, and career development. Job satisfaction is considered a crucial aspect in enhancing motivation, performance, and organizational loyalty, particularly in vocational higher education institutions that face challenges of service quality competition. Unlike quantitative studies that commonly measure job satisfaction through standardized indicators, this research adopts a qualitative approach with a case study design to explore employees’ deeper experiences and perceptions. Data were collected through in-depth interviews, direct observation, and document studies involving permanent employees who had worked for at least two years. The findings reveal that compensation and leadership have the most significant influence on job satisfaction. Employees emphasized the importance of a fair compensation system, consistent incentives, and recognition in both financial and non-financial forms. Leadership was perceived positively when it was communicative, participative, and supportive, although there were concerns regarding inconsistencies in policy communication. Meanwhile, the work environment and career development had a positive but non-significant impact. Employees acknowledged that the work atmosphere was generally conducive; however, limited physical facilities and insufficient career development opportunities created a sense of stagnation. Overall, job satisfaction at OTC Campus is understood as a balance between fair compensation, effective leadership, a supportive work environment, and opportunities for career advancement. This study provides a theoretical contribution by expanding the understanding of job satisfaction within vocational education institutions, which remain underexplored, while also offering practical implications for management to design human resource strategies that are fair, participatory, and development-oriented. Key recommendations include improving the compensation system, strengthening communicative leadership, and implementing more structured and sustainable career development programs.